Din proprietatea fundamentală a proporțiilor (produsul extremilor este egal cu produsul mezilor) obținem:
[tex]\dfrac{x - 2\sqrt{2} }{3} = \dfrac{6}{x - 2\sqrt{2}} \implies (x - 2\sqrt{2})^2 = 3 \cdot 6\\[/tex]
[tex](x - 2\sqrt{2})^2 = 18 \implies |x - 2\sqrt{2}| = \sqrt{18} \implies |x - 2\sqrt{2}| = 3\sqrt{2}\\[/tex]
[tex]1) \ x - 2\sqrt{2} = - 3\sqrt{2} \implies x = - 3\sqrt{2} + 2\sqrt{2} = -\sqrt{2}\\[/tex]
[tex]2) \ x - 2\sqrt{2} = 3\sqrt{2} \implies x = 3\sqrt{2} + 2\sqrt{2} = 5\sqrt{2}\\[/tex]
[tex]\implies \bf S = \{-\sqrt{2}; \ 5\sqrt{2}\}[/tex]
R: c)